Percutaneous Transtracheal Jet Ventilation with Various Upper Airway Obstruction. (16th June 2015) - Doi, Tomoki; Miyashita, Tetsuya; Furuya, Ryousuke; Sato, Hitoshi; Takaki, Shunsuke; Goto, Takahisa
Abstract : A "cannot-ventilate, cannot-intubate" situation is critical. In difficult airway management, transtracheal jet ventilation (TTJV) has been recommended as an invasive procedure, but specialized equipment is required. However, the influence of upper airway resistance (UAR) during TTJV has not been clarified. The aim of this study was to compare TTJV using a manual jet ventilator (MJV) and the oxygen flush device of the anesthetic machine (AM). We made a model lung offering variable UAR by adjustment of tracheal tube size that can ventilate through a 14-G cannula. We measured side flow due to the Venturi effect during TTJV, inspired tidal volume (TVi), and expiratory time under various inspiratory times. No Venturi effect was detected during TTJV with either device. With the MJV, TVi tended to increase in proportion to UAR. With AM, significant variations in TVi was not detected with changes in any UAR. In conclusion, UAR influenced forward flow of TTJV in the model lung. The influence of choked flow from the Venturi effect was minimal under all UAR settings with the MJV, but the AM could not deliver sufficient flow.